Evaluation the Rate of Correct Use of a Metered Dose Inhaler in Patients with Obstructive Lung Diseases in Ekbatan Hospital of Hamadan - Ebrahim Nadi; Fatemeh Zeraati; Ali Beigmoradi (پزشکی بالینی ابن سینا, 2002)
The aim of this study was to determine the rate of correct use of Metered Dose Inhalers (MDIs) in patients with obstructive  lung disease receiving hospital visits by internist, who checked their inhaler technique . MDIs are a convenient and popular way to administer medication (as first line drug) for life threatening asthmatic attack. Multiple studies in industrialized countries have shown that more than 50% of patients using inhalers don’t use proper technique.